2019
DOI: 10.3390/f10060463
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Propagation of Oriental White Oak Quercus aliena Blume

Abstract: Quercus aliena Blume, also known as the oriental white oak, is a widespread species in temperate forests of East Asia with significant ecological and economical importance. Establishing an efficient vegetative propagation system is important for its germplasm conservation and breeding program. Protocols of micropropagation from shoot tips and nodal segments were investigated in order to produce uniform high-quality seedlings. Nodal segments from 18 month old seedlings were used as explants to initiate the asep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…The suitability of the MS medium over WPM and B5 has also been reported by other workers, such as in Magnolia sirindhorniae (Cui et al, 2019 ), Aspilia africana (Okello et al, 2021 ), and Azadirachta indica (Bello et al, 2022 ). In contrast to our study, WPM was found as a suitable growth medium for woody tree species such as Achyrocline satureioides (Guariniello et al, 2018 ), Quercus aliena (Li et al, 2019 ), Hildegardia populifolia (Upadhyay et al, 2020 ), and Alangium salviifolium (Pandey et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 79%
“…The suitability of the MS medium over WPM and B5 has also been reported by other workers, such as in Magnolia sirindhorniae (Cui et al, 2019 ), Aspilia africana (Okello et al, 2021 ), and Azadirachta indica (Bello et al, 2022 ). In contrast to our study, WPM was found as a suitable growth medium for woody tree species such as Achyrocline satureioides (Guariniello et al, 2018 ), Quercus aliena (Li et al, 2019 ), Hildegardia populifolia (Upadhyay et al, 2020 ), and Alangium salviifolium (Pandey et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 79%
“…In contrast, when no exogenous auxin was applied, the rooting rate was only 7%. Other studies in woody species have also reported higher rooting rates with auxin: in Quercus aliena, the highest rooting rate (41%) was achieved with a combination of 4.92 µM IBA and 5 g L −1 activated carbon [26]. In the woody species Acacia confusa, 72% rooting rate was achieved by supplementing the MS culture medium with 4.92 µM IBA [27].…”
Section: Discussionmentioning
confidence: 74%
“…Both on the agar medium and on the TIS, a lower number of new shoots was observed on the modified QL medium as compared to the WPM in this study. The WPM medium is widely used during the in vitro multiplication phase for woody species during the in vitro multiplication phase of the genus Quercus [ 60 , 61 ]. Compared to QL, the WPM formulation has a higher nitrogen content, an essential macronutrient, and a structural component in plants.…”
Section: Discussionmentioning
confidence: 99%